Spillovers in networks of user generated content: Evidence from 23 natural experiments on Wikipedia - Michael E. Kummer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Endogeneity in network formation hinders the identification of the role social networks play in generating spillovers, peer effects and other externalities. This paper tackles this problem and investigates how the link network between articles on the German Wikipedia influences the attention and content generation individual articles receive. Identification exploits local exogenous shocks on a small number of nodes in the network. It can thus avoid the usually required, but strong, assumptions of exogenous observed characteristics and link structure in networks. This approach also applies if, due to a lack of network information, identification through partial overlaps in the network structure fails (e.g. in classrooms). Exogenous variation is generated by natural and technical disasters or by articles being featured on the German Wikipedia's start page. The effects on neighboring pages are substantial; I observe an increase of almost 100 percent in terms of both views and content generation. The aggregate effect over all neighbors is also large: I find that a view on a treated article converts one for one into a view on a neighboring article. However, the resulting content generation is small in absolute terms.
urn:nbn:de:bsz:180-madoc-352600
Keywords: L17; D62; D85; D29; 330; Social Media; Information; Knowledge; Spillovers; Large-scale Networks; Natural Experiment